2017
DOI: 10.1021/acs.molpharmaceut.7b00056
|View full text |Cite
|
Sign up to set email alerts
|

ImmunoPET Imaging of CTLA-4 Expression in Mouse Models of Non-small Cell Lung Cancer

Abstract: Cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) is expressed on the surface of activated T cells and some tumor cells, and is the target of the clinically-approved monoclonal antibody ipilimumab. In this study, we investigate specific binding of radiolabeled ipilimumab to CTLA-4 expressed by human non-small cell lung cancer cells in vivo using positron emission tomography (PET). Ipilimumab was radiolabeled with 64Cu (t1/2 = 12.7 h) through the use of the chelator 1,4,7,10-tetraazacyclododecane-1,4,7,10-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(49 citation statements)
references
References 27 publications
0
45
0
Order By: Relevance
“…Polymerase chain reaction (PCR)-analysis on CT26 tumor tissues from BALB/c and T cell lacking BALB/c nu/nu indicated that the CTLA-4 expression was T cell dependent and therefore the tracer could be used to image CTLA-4 positive T cells. In 2017, Ehlerding et al reported uptake of 64 Cu-labeled ipilimumab by CTLA-4 expressing human NSCLC xenografts (A549, H460, and H358) (Ehlerding et al 2017). In vivo tumor tracer uptake correlated with in vitro CTLA-4 expression levels of these tumor cells, with the highest uptake in the A549 cell line 48 h post infusion.…”
Section: Ctla-4 Imagingmentioning
confidence: 99%
“…Polymerase chain reaction (PCR)-analysis on CT26 tumor tissues from BALB/c and T cell lacking BALB/c nu/nu indicated that the CTLA-4 expression was T cell dependent and therefore the tracer could be used to image CTLA-4 positive T cells. In 2017, Ehlerding et al reported uptake of 64 Cu-labeled ipilimumab by CTLA-4 expressing human NSCLC xenografts (A549, H460, and H358) (Ehlerding et al 2017). In vivo tumor tracer uptake correlated with in vitro CTLA-4 expression levels of these tumor cells, with the highest uptake in the A549 cell line 48 h post infusion.…”
Section: Ctla-4 Imagingmentioning
confidence: 99%
“…A detailed understanding of the tumor microenvironment, including the identification and quantification of different immune cell subsets, their spatial context, and the expression of these immune checkpoint markers is obviously required to go further with these new therapies (107). Changes in immune cell infiltration and biomarker expression before and after therapeutic intervention are critical parameters for clinical development (108).…”
Section: Immune Checkpoint Inhibitors: Assessment Of Immune Status Inmentioning
confidence: 99%
“…Immuno-detection using antibodies labeled with zirconium-89 or copper-64 for PET, as well as indium-111 for SPECT, has been used to assess the CTLA-4 and PD-1 status of TIL in vivo and the expression of PD-L1 by tumor cells in order to predict the therapeutic efficacy of the administration of immune checkpoint inhibitors in mice and in human (79,(109)(110)(111). This approach was also proposed in the context of anti CTLA-4 therapy (107). Based on tumor biopsies, it appears that some patients with PD-L1-negative tumors show clinical benefit of anti-PD-L1 treatment.…”
Section: Immune Checkpoint Inhibitors: Assessment Of Immune Status Inmentioning
confidence: 99%
“…The cytotoxic T‐lymphocyte‐associated protein 4 (CTLA‐4) is a marker of immune T cells and also some lung cancer cells. The Ehlerding group162 used 64 Cu‐radiolabeled ipilimumab (anti‐CTLA‐4 mAb) for PET imaging of human NSCLC cells. In vivo results showed the radiolabeled Ab effectively accumulated in CTLA‐4 + NSCLC.…”
Section: Tumor Type‐specific Targetingmentioning
confidence: 99%